Avid 18F-FDG uptake of pectoralis major muscle: an equivocal sequela of strenuous physical exercise - Ahmad Saad, Fathinul Fikri; Lau, Eddie Wing Fai (Department of Biomedical Imaging (Radiology), Faculty of Medicine, University of Malaya, 2009)
Avid functional 18F-FDG uptake of skeletal muscle is a known false positive finding of PET-CT study especially after involuntary muscle exercise just prior to the study. We describe the case of a 50-year-old man in whom the finding of avid 18F-FDG uptake of pectoralis major muscle was encountered during investigation of metastatic melanoma.